SEISMIC ASSESSMENT AND RETROFITTING OF RC BUILDING USING CONCRETE JACKETING AND CFRP (A FINITE ELEMENT MODELLING STUDY) - talahmeh, Besan; Almassri, Belal; Ayyad, Haitham (Journal of Applied Engineering Science, 2025)
This study presents a simplified methodology for the assessment and retrofitting of an existing multistory reinforced concrete (RC) structures in Palestine, addressing the critical need for improved structural integrity in the face of increased loads and seismic risks. This study focuses on a multi-story commercial and residential building in Hebron, initially designed with seven floors, including a ground-floor store and six upper floors. The research is structured into three primary phases: preparing finite element models, performing comprehensive structural analyses to assess the feasibility of adding extra floors, evaluating the building’s seismic behavior, and exploring RC retrofitting techniques. Advanced analytical tools such as ETABS for linear analysis and SAP2000 v25 for non-linear analysis were utilized to rigorously evaluate and retrofit the seismic performance of existing multistory RC structures. The retrofitting techniques used include RC jackets and Carbon Fiber Reinforced Polymer (CFRP) applications. The findings demonstrate that the proposed methods significantly enhance structural integrity and seismic resilience. RC jacketing and CFRP retrofitting effectively eliminated plastic red hinges, ensuring column stability under additional seismic loads. The parametric study revealed that RC jacketing with a yield strength of 520 MPa achieved the highest load capacity, while CFRP retrofitting, although more expensive, offered superior stiffness and performance. This approach contributes to the safety and sustainability of urban infrastructure by extending the lifespan and functionality of existing buildings, while also providing a valuable framework for engineers and urban planners working in similar seismically active and rapidly urbanizing regions.